Study on Surgical Re-Admission in DMCH - Hussain, Md Margub; Chowdhury, Abdullah Al Mamun (Journal of Bangladesh College of Physicians and Surgeons, 2019)
Introduction: Re-admission of surgical patients following discharge from a surgical care unit to the same or different hospital is not uncommon. Underlying causes varied. Majority of re-admission are unplanned. Postoperative complications are mainly responsible for patients to seek re-admission. Post operative complications are the mainly liable for surgical re-admission. Methods: A prospective study was performed in General Surgical units of Dhaka Medical College Hospital, Dhaka for one year from August’2011 to July’2012. Amongst the patients admitted in surgical units, all re-admitted patients within the period had been studied. Purposive sampling was done. Rate, cause, avoidability etc. were studied according to criteria. Results: Among 4396 admitted patients 294 (7%) had history of previous admission in surgical department of different hospitals. 65% patients were male and 70.07% were middle aged (20-50yr). 67% re-admisssion occurred through emergency department of which 67.7% were unplanned. 58% re-admission were avoidable. Diagnosis at readmission contains quite a long list but notables were loop ileostomy (23.47%), enterocutaneous fistula (10.54%), incisional hernia (9.52%), mature colostomy (8.84%), wound infection (8.5%) and subacute intestinal obstruction (4.76%). Conclusion: Re-admission can be a contributing factor to assess quality and performance. It should be focused in audit and practice. J Bangladesh Coll Phys Surg 2019; 37(2): 54-59